2021
DOI: 10.17221/258/2020-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of minerals between orange juice and orange flesh in various cultivars

Abstract: The aim of this study was to evaluate the distribution of essential and toxic elements between the orange juice and orange flesh of various orange cultivars. Different orange cultivars, such as Abousorah [Citrus sinensis (L.)], Aseear (Citrus aurantium), Afandi (Citrus reticulata Blanco), Helo (Citrus sinensis), and grapefruit (Citrus paradisi), were collected from local markets. Elemental analysis was carried out after microwave-assisted digestion using inductively coupled plasma mass spectrometry (ICP-MS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…Thus, there were no health risks posed by the consumption of these fruits. Our results were dissimilar from the findings of Brima and Mohamed [54], who reported that the concentrations of Pb in the fruit juice of C. reticulata and C. paradisi were 0.29 ± 0.16 and 0.10 ± 0.004 mg/kg, respectively. Elbagermi et al [51] described similar mean con-centrations of the metals Pb and Cd, with values of 0.20 ± 0.04 and 0.03 ± 0.02 mg/kg, respectively, in orange fruit samples.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, there were no health risks posed by the consumption of these fruits. Our results were dissimilar from the findings of Brima and Mohamed [54], who reported that the concentrations of Pb in the fruit juice of C. reticulata and C. paradisi were 0.29 ± 0.16 and 0.10 ± 0.004 mg/kg, respectively. Elbagermi et al [51] described similar mean con-centrations of the metals Pb and Cd, with values of 0.20 ± 0.04 and 0.03 ± 0.02 mg/kg, respectively, in orange fruit samples.…”
Section: Discussioncontrasting
confidence: 99%
“…The amount of Cr in the fruit samples was far below the maximum allowable limit of 2.3 mg/kg [51]. Our results were consistent with the findings of Brima and Mohamed [54], who reported that the concentrations of Cr in the fruit juice of C. reticulata and C. paradisi were 0.20 ± 0.08 and 0.77 ± 0.05 mg/kg, respectively. Ghani et al [26] showed that the concentration of Cr fluctuated from 0.031 to 0.342 mg/kg in different tehsils of the Sargodha district.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Almeelbi et al [13] also reported different Zn concentrations in citrus fruit samples irrigated with SW (0.321 ± 0.021 µg/g) and TW (0.032 ± 0.001 µg/g). However, Brima and Mohamed [56] reported Zn concentrations of 0.78 ± 0.36 mg/kg in C. reticulata and 7.17 ± 2.93 mg/kg in C. paradisi in their fruit juice. Ghani et al [24] stated that the concentration of Zn fluctuated from 26.463 ± 1.57 to 31.726 ± 1.31 mg/kg in different tehsils of the Sargodha district with the highest amount reported in tehsil Silanwali.…”
Section: Discussionmentioning
confidence: 95%
“…Rasool et al [55] had similar results for Mn in C. paradisi (0.52 ± 0.05 mg/kg) and C. reticulata (0.40 ± 0.04 mg/kg) in Sargodha. Brima and Mohamed [56] reported that the concentration of Mn in C. reticulata and C. paradisi was 0.33 ± 0.09 and 4.57 ± 0.6 mg/kg, respectively, in the fruit juice of the two varieties. Ghani et al [24] stated that the quantity of Mn varied from 0.051 ± 0.01 to 0.163 ± 0.05 mg/kg in different tehsils of the Sargodha district; the highest concentration of Mn was present in tehsil Silanwali in the Sargodha district.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation